A Comparison Between the Patterns of CN, O, and Na Inhomogeneities on the Red Giant Branch of 47 Tucanae. (4th January 2016) - Smith, Graeme H.
Abstract: Data from the literature are drawn together to compare the λ4215 CN band strength of red giant stars in the globular cluster 47 Tucanae with their sodium and oxygen abundances. Most cluster giants included in this study have absolute magnitudes brighter than M V  = +0.5, i.e., they are brighter than the horizontal branch. Among the majority of these cluster giants, it is possible to identify an anticorrelation between the CN band strength and the [O/Fe] abundance, along with a correlation between CN band strength and [Na/Fe], although a small number of stars seem to be exceptions to these trends. As regards the CN-weak and CN-strong populations of red giants in 47 Tuc, the former has a higher mean oxygen abundance and a lower mean sodium abundance than the later. Both populations may contain a small fraction of stars whose sodium or oxygen abundances differ by ∼0.2 dex from the mean of each population. A scenario is discussed in which 47 Tuc was the result of an early merger between a CN-poor and a CN-strong subcluster of stars that formed at different locations within the interior of a chemically evolving massive gas complex.